Rétegmobilitás, státuszmobilitás és felekezeti vegyesházasság Budapesten a két világháború között - Karády, Viktor (Szociológiai Szemle, 2024)
The study aims to assess the social significance of the mixed marriages on the basis of analysing statistical sources of extraordinary value. The mixed marriage is analysed as a way of social mobility through marriage. Significant results are obtained primarily from the analysis of mixed Jewish-Christian marriages; the study investigates the social distance between the denomations, the effects of secularization, the status mobility, the inequalities in the position of men and women and also the unequal share of „investing” in the marriage. The author draws the conclusion that the conditions, determined by forced assimilation and class-status exert a decisive influence on choosing marriage-partners, though of course these decisions are always subjective decisions which can never be fully rationalized.